Infliximab three-dose induction regimen in severe corticosteroid-refractory ulcerative colitis: Early and late outcome and predictors of colectomy. (1st August 2014) - Monterubbianesi, Rita; Aratari, Annalisa; Armuzzi, Alessandro; Daperno, Marco; Biancone, Livia; Cappello, Maria; Annese, Vito; Riegler, Gabriele; Orlando, Ambrogio; Viscido, Angelo; Meucci, Gianmichele; Gasbarrini, Antonio; et al.
Abstract: Background: Infliximab is effective as rescue therapy in severe corticosteroid-refractory ulcerative colitis. The optimal dose regimen and the long term benefits are not well defined. The aim of the present study was to evaluate short- and long-term colectomy rate in a cohort of patients with severe corticosteroid-refractory ulcerative colitis who received a three-dose infliximab induction regimen. Methods: One hundred and thirteen patients admitted to 11 Italian IBD referral centres and treated with infliximab according to an intention to treat three-dose regimen were included. The co-primary endpoints were 3- and 12-month colectomy rate. The secondary end-points were the overall colectomy-free survival and the identification of predictors of colectomy. Results: The 3- and 12-month colectomy rates were 18.6% (95%CI 11.8%–26.9%) and 25.6% (95%CI 17.9%–34.7%) respectively. High CRP values and severe endoscopic lesions were associated with the risk of colectomy: Risk Ratio (RR) = 2.15 (95%CI 1.05–4.36), and RR = 5.13 (95%CI 1.55–16.96), respectively. In patients escaping early colectomy, the probability of a colectomy-free course at 12, 24, 36 and 60 months was 91%, 85%, 81% and 73%, respectively. Endoscopic severity was the only predictor of long term colectomy (RR = 7.0; 95%CI 1.09–44.7). Adverse events occurred in 16 patients (14%); there was one death (0.88%) due to pulmonary abscess. Conclusions: Infliximab is an effective and safe rescue therapy for severe corticosteroid-refractory ulcerative colitis. A three-dose induction regimen seems to be the treatment of choice for preventing early colectomy. Severe endoscopic lesions appear to be predictor of short- and long-term colectomy.